GENOTYPIC CHARACTERIZATION OF COLISTIN RESISTANCE GENES AMONG MULTIDRUG-RESISTANT GRAM-NEGATIVE BACILLI IN A TERTIARY-CARE CENTRE: MOLECULAR CORRELATION WITH PHENOTYPIC PROFILES - Ms Ashma Ajeej; Dr Ramanath Karicheri (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Colistin resistance among multidrug-resistant Gram-negative bacilli (MDR-GNB) is an emerging global concern, threatening the efficacy of last-resort antibiotics. The detection of plasmid-borne mcr genes revolutionized the understanding of colistin resistance, indicating horizontal transfer potential among bacterial species¹.Objectives:To characterize colistin-resistance genes (mcr-1–mcr-10, pmrA/B, mgrB, phoP/Q, lpxA/C/D) among MDR-GNB isolated in a tertiary-care centre, correlate genotypic findings with phenotypic MICs, and analyze epidemiological implications.Methods:A total of 150 MDR-GNB isolates (Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii) were collected. Colistin MICs were determined by broth microdilution (BMD) as per CLSI 2024 guidelines². Genomic DNA was extracted (Qiagen Mini Kit) and PCR targeted mcr-1–mcr-10¹², mgrB, pmrA/B, phoP/Q, and lpxA/C/D³. Amplicons were sequenced and analyzed via BLAST⁴. Plasmid profiling (S1-PFGE, replicon typing)¹⁴ and clonal relatedness (ERIC-PCR)¹⁵ were performed.Results:Twenty (13.3%) isolates were phenotypically colistin-resistant. mcr-1 (4%) and mcr-3 (2%) were detected, mainly in K. pneumoniae and E. coli ⁶. mgrB disruption (IS5 insertion) occurred in five K. pneumoniae¹⁷; pmrB mutations (A79V, R256G) in A. baumannii¹⁸. Genotype–phenotype concordance was 86%. ERIC-PCR revealed two ICU clusters, indicating nosocomial dissemination via IncX4 plasmids.Conclusion:Colistin resistance in MDR-GNB results from both plasmid-mediated mcr genes and chromosomal mutations (mgrB, pmrB). Combined phenotypic and molecular surveillance under WHO GLASS is essential for accurate detection and infection-control interventions.